2003
DOI: 10.1007/s00122-002-1118-7
|View full text |Cite
|
Sign up to set email alerts
|

Reproduction and cytogenetic characterization of interspecific hybrids derived from Cucumis hystrix Chakr. × Cucumis sativus L.

Abstract: Interspecific hybrids between Cucumis hystrix Chakr. (2n = 2 x = 24) and Cucumis sativus L. (2n = 2 x = 14) were produced by means of F(1) (2n = 19) embryo rescue and subsequent chromosome doubling. The hybridity was confirmed by genomic in situ hybridization (GISH) and chromosome analysis. The amphidiploid (2n = 38) was self-pollinated and backcrossed to cucumber resulting in lines with improved crossability to C. sativus. Examination of shape, stainability, and germination rate of pollen grains and yield as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
45
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 12 publications
1
45
0
Order By: Relevance
“…sativus (Chen et al 1997b). Cucumis hystrix appears to possess economically important traits such as root-knot nematode resistance (Chen and Lewis 2000;Chen et al 2001), gummy stem blight (D. bryoniae) resistance, downy mildew (P. cubensis) resistance, unique nutritional qualities, and tolerance to growth under low irradiance and temperature (Chen et al 2003b;Chen, Moriarty, and Jahn 2004b).…”
Section: Cross-incompatible Breeding Strategiesmentioning
confidence: 99%
See 2 more Smart Citations
“…sativus (Chen et al 1997b). Cucumis hystrix appears to possess economically important traits such as root-knot nematode resistance (Chen and Lewis 2000;Chen et al 2001), gummy stem blight (D. bryoniae) resistance, downy mildew (P. cubensis) resistance, unique nutritional qualities, and tolerance to growth under low irradiance and temperature (Chen et al 2003b;Chen, Moriarty, and Jahn 2004b).…”
Section: Cross-incompatible Breeding Strategiesmentioning
confidence: 99%
“…sativusX C. hystrix matings, indicating maternal and paternal inheritance for certain morphological and molecular (RAPD) characters (Chen et al 2004c). The resulting amphidiploid (HHCC, 2n = 4x = 38) was designated as a new synthetic nothospecies (C. Xhytivus Chen) and has been reproduced in subsequent experiments, ultimately resulting in an array of amphidiploids that have been self-pollinated to produce viable seeds (Chen and Kirkbride 2000;Chen et al 2003b). More recently, hybridization experiments have produced allotriploids (2n=3x=26; genome designated as HCC) from amphidoploidXdiploid (C. sativus var.…”
Section: Cross-incompatible Breeding Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In cytogenetic field, cucumber's chromosomes were studied in order to demonstrate their genomic characters (Trivedi and Roy 1970, Ramachandran and Seshadri 1986, Chen et al 2003, Tagashira et al 2006. The most standard references demonstrated that Cucumis sativus had the chromosome number of 2n=14, which was different from that of the other species of Cucumis (Dane and Tsuchiya 1976;Dane et al 1980).The basic karyotype was analyzed by the conventional method (Trivedi and Roy 1970;Sing and Roy 1974;Dane and Tsuchiya 1976;Ramachandran and Seshadri 1986;Hoshi et al 1998) and differential staining method such as C-banding method (Ramachandran and Seshadri 1986;Chen et al 1998;Hoshi et al 1998;Koo et al 2002), chromomycin A 3 (CMA) method and 4',6-diamidino-2-phenylindole (DAPI) staining method Hoshi et al 1999;Hoshi et al 2008).…”
mentioning
confidence: 99%
“…[47], Cucumis sp. [48]). However, for numerous plant groups such approaches are very laborious and/or have low or no success (e.g.…”
Section: Wild-to-crop Bridgesmentioning
confidence: 99%